Solve for z (z-3)/6=8/12

Math
z-36=812
Multiply both sides of the equation by 6.
6⋅z-36=6⋅812
Simplify both sides of the equation.
Tap for more steps…
Cancel the common factor of 6.
Tap for more steps…
Cancel the common factor.
6⋅z-36=6⋅812
Rewrite the expression.
z-3=6⋅812
z-3=6⋅812
Simplify 6⋅812.
Tap for more steps…
Cancel the common factor of 6.
Tap for more steps…
Factor 6 out of 12.
z-3=6⋅86(2)
Cancel the common factor.
z-3=6⋅86⋅2
Rewrite the expression.
z-3=82
z-3=82
Divide 8 by 2.
z-3=4
z-3=4
z-3=4
Move all terms not containing z to the right side of the equation.
Tap for more steps…
Add 3 to both sides of the equation.
z=4+3
Add 4 and 3.
z=7
z=7
Solve for z (z-3)/6=8/12

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top